Digitalization and the Global Competitiveness of Exported Services - Sipakoly, Selly (SAFE-Network, 2025)
As global trade increasingly shifts toward services, many countries struggle to remain competitive in digitally driven markets due to infrastructural gaps, regulatory fragmentation, and firm-level disparities. This literature review investigates how digitalization reshapes the global competitiveness of exported services. Based on 58 peer-reviewed studies published between 2015 and 2024, the analysis identifies four recurring themes: digital infrastructure, firm-level digital capabilities, regulatory and institutional environments, and structural barriers. Findings show that while digitalization facilitates service scalability, market access, and innovation, competitiveness remains uneven and contingent on a country’s or firm’s ability to align digital assets with institutional coherence and strategic readiness. The review highlights that to enhance digital service competitiveness, governments must prioritize inclusive infrastructure investment, support SMEs in acquiring digital capabilities, harmonize cross-border digital regulations, and mitigate risks tied to platform dependency and cybersecurity. These implications point to the need for coordinated policy responses and long-term strategies that build digital resilience and equitable participation in global service trade.